Haemodynamic analysis for recanalisation of intracranial aneurysms after endovascular treatment: an observational registry study in China. Issue 5 (12th May 2017) - Liu, Jian; Zhang, Yisen; Wang, Anxin; Zhang, Ying; Li, Yiying; Yang, Xinjian
Abstract : Introduction: Recanalisation of intracranial aneurysms following endovascular treatment is a major issue. Many factors, including aneurysm morphology, the method of treatment, and haemodynamics, are considered to be associated with recanalisation. However, the underlying haemodynamic mechanisms are not completely understood. Methods and analysis: This is a prospective, observational, registry study for patients with intracranial aneurysms who are treated endovascularly. It will enrol 200 eligible patients. Data on morphological, haemodynamic, and treatment factors will be collected prospectively. The advanced virtual stenting technique and porous media method will be used in haemodynamic simulations. The clinical and angiographic outcomes at 6 months will be measured and analysed. This observational study will determine the haemodynamic factors that affect the recanalisation of aneurysms. Ethics and dissemination: Both the study protocol and written informed consent were reviewed and approved by the Institutional Review Board of Beijing Tiantan Hospital (KY2016-023-01). The results of study will be disseminated in professional printed media. Trial registration number: NCT02812108 ; Pre-results.